PEMBELAJARAN KOMPOSISI UNTUK BIDANG KONSENTRASI POP-JAZZ DALAM KURIKULUM SARJANA MUSIK - B. Koapaha, Royke (PROMUSIKA, 2013)
This article is worked to support the undergraduate study program revitalization of Music Department, The Facuty of Performing Arts, ISI Yogyakarta, especially in developing creative industry weight through composition training into the Pop-Jazz subjects package, wich is one among the five elective sub competency packages provide by the curriculum. Basically, the author offers composition subject material that is estimated beneficial in developing creative industry in Pop-Jazz program of the Department Keywords: Creative industry, composition, pop-jazz